(untitled) (Czech Journal of Multidisciplinary Innovations, 2022)
The article explores organizational and theoretical issues, features and foreign experience in the development of remote banking services in the context of the introduction of the digital economy. Also, the current state and further development of remote banking services in commercial banks in the context of digitalization of banking services are considered, ideas, scientific proposals and recommendations of the author on the above issues are presented.